Effectiveness of Vetiver (Vetiveria zizanioides) Application with Modular System in Soil Bioengineering for Soil Reinforcement - Nurmansyah, Muhammad Reza; Putra, Heriansyah; Arif, Chusnul (Journal of Geoscience, Engineering, Environment, and Technology, 2026)
Indonesia has a diverse topography characterized by many hilly and mountainous regions, rendering it vulnerable to landslides. BNPB data indicate that, in 2024, there were 207 landslide incidents in Indonesia. Soil bioengineering methods using vetiver plants can improve soil stability. This study aimed to evaluate the effectiveness of vetiver application via a modular soil stabilization system using soil bioengineering. The research was conducted by testing soil properties, followed by planting vetiver in 10-cm-diameter pipes 50 cm high, with a geotextile measuring 10 × 10 × 10 cm on top containing a mixture of soil and planting media. Subsequently, maintenance, soil shear strength testing, and root dimension observations were performed on samples aged 1, 2, and 3 months after planting (MAP). The test results showed that the root growth rate increased by 30–40 cm in vetiver samples in the modular system. The most significant increase in soil shear strength was observed in the cohesion parameter, reaching 19.55 kPa. Therefore, vetiver roots contributed to the greatest increase in cohesion (c), reaching 8.57 kPa. The application of vetiver significantly increases soil shear strength, making it suitable for use as a slope reinforcement method.